2022
DOI: 10.3390/fermentation8110593
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomic Analysis of Bacillus subtilis and Aspergillus niger in Black Soldier Fly Co-Fermentation

Abstract: Black soldier fly larvae have gained popularity as an organic waste bio-conversional tool and fodder protein replacement in recent decades. It can consume all kinds of animal feces, kitchen waste and agricultural waste with great efficiency and transform them into high-value insect protein, fatty acids, and amino acids, which makes the larva a good substitute for costly fish meal and bean pulp in animal diets. However, excess chitin in the larva skin limits its application as an animal feed additive, consequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Liu et al . (2022) found A. fumigatus activates several lyases when no other polysaccharide is detected to break down chitin to obtain chitooligosaccharides as an energy source and fungal cell wall material for adaptation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al . (2022) found A. fumigatus activates several lyases when no other polysaccharide is detected to break down chitin to obtain chitooligosaccharides as an energy source and fungal cell wall material for adaptation.…”
Section: Resultsmentioning
confidence: 99%
“…Studies found that species of Aspergillus such as A. nigger and A. fumigatus produce extracellular chitinases when shrimp and crab shells and colloidal chitin are used as substrate (Abdel & Esawy, 2022;Abdel et al, 2023). Liu et al (2022) found A. fumigatus activates several lyases when no other polysaccharide is detected to break down chitin to obtain chitooligosaccharides as an energy source and fungal cell wall material for adaptation.…”
Section: Protein and Chitin Contentmentioning
confidence: 99%